A meiosis-specific BRCA2 binding protein recruits recombinases to DNA double-strand breaks to ensure homologous recombination - Jingjing Zhang (Nature Portfolio, 2019)
Homology directed repair of meiotic double-strand breaks functions via recruitment and assembly of strand-exchange proteins called recombinases. Here the authors reveal and characterize a BRCA2 interactor regulating meiotic recombinases that localizes to chromosomal axes and facilitates the repair of meiotic DSBs.